Parasitismo de Erythmelus tingitiphagus (Soares) (Hymenoptera: Mymaridae) em ovos de Leptopharsa heveae Drake & Poor (Hemiptera: Tingidae), em plantios de seringueira (Hevea brasiliensis Müell. Arg.) - Santos, Rodrigo S. [UNESP]; de Freitas, Sergio [UNESP] (Entomological Soc Brasil, 2008)
The rubber tree lace bug, Leptopharsa heveae Drake & Poor occurs in high populations in rubber tree plantations and it is a limiting factor in rubber production due to the loss of photosynthetic tissue. The control of the pest has been made mainly with chemical products, which cause environmental contamination. The alternative would be the use of biological control agents, however, information about L. heveae natural enemies are scarce. The parasitoid Erythmelus tingitiphagus (Soares) parasitize eggs of the rubber tree lace bug. The aim of this study was to verify the occurrence of E. tingitiphagus in plantations of several rubber tree clones, located in Itiquira town, Mato Grosso State. The plant leaflets of the clones RRIM 600, PR 255, GT 1, PB 235 and PB 217 were collected weekly from October 2005 to February 2006. Parasitism was recorded during the entire study period. The parasitism rate of L. heveae eggs in the different clones ranged from 16.8 to 20.6%.
Parasitism of Erythmelus tingitiphagus (Soares) (Hymenoptera: Mymaridae) in Leptopharsa heveae Drake & Poor (Hemiptera: Tingidae) Eggs, in Rubber Tree Plantation (Hevea brasiliensis Muell. Arg.)
Keywords: Chalcidoidea; Biological control; Heveiculture